Preparation method of carbon nanotube film with high thermoelectric performance

By ultrasonic dispersing in the carbon nanotubes and lignin solution and removing unbound lignin by centrifugation, the problem of easy agglomeration of carbon nanotubes is solved, its dispersion and thermoelectric properties are improved, and efficient preparation of thermoelectric materials is achieved.

CN119522019APending Publication Date: 2025-02-25WUHAN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411358444.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-03
Filing Date
2024-09-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Carbon nanotubes are prone to agglomeration in aqueous solution, affecting their dispersion and thermoelectric properties. The existing methods require the addition of surfactants to increase process costs and non-conductive lignin affects the conductive properties of carbon nanotubes.

Method used

High thermoelectric carbon nanotubes are prepared by mixing carbon nanotubes with lignin solution, ultrasonic dispersion, and centrifuging to remove unbound lignin.

Benefits of technology

It improves the dispersion and thermoelectric properties of carbon nanotubes, reduces the use of surfactants, reduces process costs, and improves the electrical and thermoelectric properties of carbon nanotube membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522019A_ABST
    Figure CN119522019A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of thermoelectric materials, and particularly relates to a preparation method of a carbon nanotube film with high thermoelectric performance. The preparation method comprises the following steps: uniformly mixing carbon nanotubes with a lignin solution, and carrying out ultrasonic dispersion to obtain a carbon nanotube dispersion liquid; centrifuging the carbon nano tube dispersion liquid until the carbon nano tubes in the carbon nano tube dispersion liquid are settled, removing supernate, dispersing in ammonia water, dispensing on a slide substrate, and drying to obtain the carbon nano tube film. According to the method, lignin is adopted to disperse the carbon nanotubes and is removed through centrifugation, the problem that the carbon nanotubes are prone to agglomeration in an aqueous solution is solved, meanwhile, the influence of non-conductive lignin on the electrical properties of the carbon nanotubes is removed, and the dispersity and thermoelectric properties of the carbon nanotubes are synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thermoelectric materials, and in particular to a method for preparing a carbon nanotube film with high thermoelectric performance. Background Art

[0002] Environmental pollution and resource shortages are the main problems facing mankind in the 21st century. Finding clean and sustainable new energy is a key issue for future social progress and development. In industrial production and daily life, only 30% of the energy generated by the combustion of fossil energy can be effectively utilized, and the rest is directly discharged into the atmosphere in the form of waste heat. Thermoelectric materials can utilize the movement of internal carriers to achieve direct conversion of thermal energy and electrical energy, improve energy conversion efficiency, and are receiving more and more attention. The thermoelectric performance of materials is usually measured by the dimensionless thermoelectric figure of merit ZT or power factor (PF), PF = S 2 σ, where S is the Seebeck coefficient and σ is the electrical conductivity. The higher the PF value, the higher the thermoelectric conversion efficiency of the material, which is more conducive to the efficient conversion of thermal energy into electrical energy. Therefore, if you want to improve the thermoelectric performance of the material, you must synergistically improve the material's electrical conductivity and Seebeck coefficient.

[0003] Carbon nanotubes have the characteristics of high carrier mobility, super hydrophilicity, high thermal conductivity and high strength. Due to their excellent σ and mechanical properties, they show great application potential in the field of thermoelectrics. However, due to the strong van der Waals force, carbon nanotubes do not exist in the form of discrete particles, but aggregate into bundles and entangle into clusters. In addition, the chemical inertness of carbon nanotubes themselves and the weak interaction between them and solvents or polymer matrices make it difficult for carbon nanotubes to disperse in solvents or polymers. These factors seriously restrict charge conduction and thermoelectric applications. In order to eliminate large agglomerates and improve the dispersion properties of carbon nanotubes, different additives are usually added to carbon nanotubes to help disperse and improve their thermoelectric properties. MFIslam et al. used anionic surfactants sodium dodecylbenzene sulfonate (SDBS), sodium dodecyl sulfate (SDS) and nonionic surfactant Triton X-100 to treat carbon nanotubes and improve their dispersibility (Nano letters, 2003, 3, 260.). A.Hajian et al. used nanocellulose as a dispersant for carbon nanotubes, dispersing carbon nanomaterials in water to form a long-term stable colloidal dispersion. The charge on nanocellulose causes electrostatic stabilization of the nanocellulose-carbon nanotube complex, thereby preventing aggregation and further improving the dispersion of carbon nanotubes. When the carbon nanotube content is 75wt%, the conductivity of the composite material reaches 515Scm -1 (Nano Letters, 2017,17,1439.).

[0004] As the second most abundant natural polymer in the plant kingdom, lignin has the advantages of being non-toxic, environmentally friendly, and green and renewable. Its unique amphiphilic properties and conjugated structure enable it to form π-π interactions with carbon nanotubes or graphite, thereby effectively dispersing carbon materials. Chinese invention patent application CN201810324633.6 discloses a method for preparing a carbon nanotube dispersion, which uses lignin sulfonate and carbon nanotubes for grinding and adding a stabilizer for ultrasonic dispersion to obtain a carbon nanotube aqueous dispersion. Chinese invention patent application CN201911351454.2 discloses a method for improving the stability of carbon nanotubes, wherein the carbon nanotubes are heated with mixed acid to remove impurities and then soaked in ethanol, filtered and dried to obtain carbon nanotubes A. Then, carbon nanotubes A are added to an aqueous solution of ethanol, mixed evenly, lignin sulfonate is added, heated and stirred for 1-3 hours, and then a surfactant is added to obtain a stably dispersed carbon nanotube dispersion. Although these methods can improve the dispersibility of carbon nanotubes, surfactants such as sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and hexadecyltrimethylammonium bromide need to be added during the preparation, which is not conducive to charge conduction and increases process costs. In addition, lignin in the carbon nanotube dispersion is an insulating macromolecule, which affects the conductivity and thermoelectric properties of carbon nanotubes.

[0005] Therefore, based on the combination of lignin and carbon nanotubes, it is necessary to obtain lignin-carbon nanotube materials with excellent thermoelectric properties by optimizing the components and / or preparation process in the material. Summary of the invention

[0006] In view of the above defects or improvement needs of the prior art, the present invention provides a method for preparing a high thermoelectric carbon nanotube film. The present invention uses lignin to disperse carbon nanotubes and uses centrifugation to remove lignin, thereby solving the problem that carbon nanotubes are easy to agglomerate in aqueous solution, and at the same time removes the influence of non-conductive lignin on the electrical properties of carbon nanotubes, synergistically improving the dispersion and thermoelectric properties of carbon nanotubes, thereby solving the problem that existing carbon nanotubes are easy to agglomerate and affect electrical and thermoelectric properties.

[0007] To achieve the above object, a first aspect of the present invention provides a method for preparing a high thermoelectric carbon nanotube film, comprising the following steps:

[0008] The carbon nanotubes and the lignin solution are uniformly mixed and ultrasonically dispersed to obtain a carbon nanotube dispersion;

[0009] The carbon nanotube dispersion is centrifuged until the carbon nanotubes in the carbon nanotube dispersion are precipitated, the supernatant is removed, the carbon nanotubes are dispersed in a solvent, and the solvent is drop-coated on a glass substrate, and dried to obtain a carbon nanotube film.

[0010] As a preferred embodiment of the present invention, the mass ratio of the lignin to the carbon nanotubes is (0.05-0.6):1.

[0011] As a preferred embodiment of the present invention, the mass concentration of the lignin solution is 0.1-3 mg / mL; the molecular weight of the lignin solution is 500-10000.

[0012] As a preferred embodiment of the present invention, the lignin solution is obtained by dissolving lignin in an alkaline solution to prepare a lignin solution;

[0013] The alkaline solution is one of sodium hydroxide, potassium hydroxide and ammonia water, and the concentration of the alkaline solution is 0.1-1M.

[0014] As a preferred embodiment of the present invention, the carbon nanotubes are one or more of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes; the inner diameter of the carbon nanotubes is less than 2 nm, and the length is 5-30 μm.

[0015] As a preferred embodiment of the present invention, the power of the ultrasonic dispersion is 70-300W, and the ultrasonic time is 1-60min.

[0016] As a preferred embodiment of the present invention, the centrifugal rotation speed is 5000-12000r / min, and the time is 1-30min.

[0017] As a preferred embodiment of the present invention, the solvent is water or an alkaline solution.

[0018] As a preferred embodiment of the present invention, the drying temperature is 60-100° C. and the drying time is 1-5 h.

[0019] In another aspect of the present invention, there is provided a carbon nanotube film with high thermoelectric performance prepared by the preparation method as described in the first aspect of the present invention.

[0020] In another aspect of the present invention, there is provided a use of a carbon nanotube film with high thermoelectric performance as a thermoelectric material as provided in the first aspect of the present invention.

[0021] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0022] (1) The present invention provides a method for preparing a carbon nanotube film with high thermoelectric properties, which comprises dispersing carbon nanotubes in a lignin solution, removing unbound lignin by centrifugation, and drying to prepare a carbon nanotube film with high thermoelectric properties. The addition of lignin in the present invention effectively reduces carbon nanotube agglomeration, improves the degree of dispersion of carbon nanotubes in the dispersion and film, and thus promotes charge transfer, thereby improving the electrical and thermoelectric properties of the carbon nanotube film. At the same time, unbound lignin is removed by centrifugation, reducing the effect of insulating additives on the thermoelectric properties of carbon nanotubes, thereby synergistically improving the electrical and thermoelectric properties of existing carbon nanotubes that are easily agglomerated.

[0023] (2) The preferred mass ratio of lignin to carbon nanotubes in the present invention is (0.05-0.6):1, so that the lignin-carbon nanotube film has good dispersibility and excellent thermoelectric performance. In particular, compared with the specific preparation method without centrifugation, the upper limit of the mass ratio of lignin to carbon nanotubes in the present invention is higher, resulting in better corresponding thermoelectric performance.

[0024] (3) In the process of preparing the carbon nanotube film of the present invention, the raw material used is green and environmentally friendly lignin, and no other surfactants and stabilizers are needed, and weak bases are used to avoid toxic and harmful organic solvents and concentrated acids, concentrated bases and strong oxidants. Compared with the preparation methods involved in the prior art, there are certain requirements for solvents and process control.

[0025] Furthermore, the preparation process of the present invention is simple, and the carbon nanotube film is prepared by a drop coating process, and the film thickness and size can be precisely controlled. Therefore, the preparation cost of the present invention is low, the controllability is high, the stability is excellent, the performance-price ratio is excellent, and it is suitable for large-scale industrial production.

[0026] (4) Furthermore, the carbon nanotube dispersion prepared by the present invention has good dispersibility and a wide range of applications, and can be used as an additive and combined with other materials to prepare high value-added functional composite films.

[0027] In summary, the present invention uses lignin to disperse carbon nanotubes and uses centrifugation to remove lignin, thereby solving the problem that carbon nanotubes are easy to agglomerate in aqueous solution, while removing the influence of non-conductive lignin on the electrical properties of carbon nanotubes, and synergistically improving the dispersion and thermoelectric properties of carbon nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a comparison photo of the lignin-dispersed carbon nanotube dispersion obtained in Example 1 of the present invention and the original carbon nanotubes;

[0029] Figure 2 This is a photo of the lignin-carbon nanotube film prepared in Example 1 of the present invention;

[0030] Figure 3 This is a scanning electron microscope image of the lignin dispersed carbon nanotube film obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0032] The present invention provides a preparation method for improving the thermoelectric performance of a carbon nanotube film, which is prepared by uniformly dispersing carbon nanotubes into a lignin solution and removing unbound lignin by centrifugation. The details are as follows:

[0033] Lignin is dissolved in an alkaline solution to obtain a lignin solution, wherein the mass concentration of the lignin solution is 0.1-3mg / mL, the molecular weight of the lignin is 500-10000, the alkaline solution is one of sodium hydroxide, potassium hydroxide, and ammonia, and the alkaline solution concentration is 0.1-1M. Carbon nanotubes are added to the lignin solution and mixed uniformly, and ultrasonic dispersion is performed to obtain a stably dispersed carbon nanotube dispersion liquid. The added mass ratio of lignin to carbon nanotubes is (0.05-0.6): 1, and the carbon nanotubes are one or more of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes. Cell crusher ultrasound is used, and the ultrasonic power is 70-300W, and the ultrasonic time is 1-60min. Further, the carbon nanotube dispersion liquid is centrifuged to allow the carbon nanotubes to settle, and the supernatant is removed to remove the unbound lignin therein. After the carbon nanotubes are dispersed in ammonia water, the dispersed liquid droplets are applied to a glass substrate, placed on a hot stage, and heated at 60-100° C. for 1-5 hours for drying to obtain a carbon nanotube film with good dispersion and excellent thermoelectric properties.

[0034] The thermoelectric performance test of the carbon nanotube film prepared by the above method, or the material obtained or prepared by other methods, is as follows:

[0035] Conductivity (σ) test: First, the resistance of the carbon nanotube film is measured by the four-probe method, and then the film thickness is measured using a step profiler. The conductivity is obtained according to the formula The carbon nanotube film was connected to a digital source meter to measure the resistance Rs. The film was then scratched and the height difference between the film and the glass substrate was measured using a step profiler to obtain the film thickness (d). The conductivity was finally calculated by substituting it into the formula.

[0036] Seebeck coefficient (S) test: Place two copper wires dipped in a small amount of silver paste in parallel on the film surface. The copper wires are used as electrodes to connect a multimeter to test the thermal voltage (ΔV). One end of the film is placed on a Peltier plate for heating, and the other end is placed in the environment to generate a temperature gradient (ΔT). Change the temperature gradient and test the voltage difference under different temperature differences. Record 6 sets of temperature difference and voltage difference values ​​for each film, make a scatter plot of the data and make a linear fit ΔV / ΔT, the slope of which is the Seebeck coefficient.

[0037] Thermoelectric performance is evaluated by the thermoelectric figure of merit ZT or power factor (PF), PF = S 2σ, the higher the power factor, the higher the thermoelectric conversion efficiency, and the more conducive to the efficient conversion of thermoelectricity to electrical energy. Therefore, improving the power factor is conducive to the development of high thermoelectric performance materials, which has important practical significance for the collection of waste heat and the efficient use of energy.

[0038] Some embodiments will be specifically given below, and detailed description will be given in conjunction with the accompanying drawings. The examples are only used to explain the present invention, and are not used to limit the scope of the present invention.

[0039] Embodiment 1:

[0040] 1 mg of lignin was added to 2 mL of 0.5 M ammonia solution and stirred at room temperature for 3 h to obtain a lignin solution. 6 mg of carbon nanotubes were added to the lignin solution, mixed evenly, and then ultrasonicated with a cell crusher at a power of 150 W for 5 min to obtain a stably dispersed carbon nanotube dispersion.

[0041] like Figure 1 , which are comparison photos of the lignin-dispersed carbon nanotube dispersion (carbon nanotube / lignin dispersion) obtained in Example 1 and the original carbon nanotubes; Figure 1 The carbon nanotube / lignin dispersion shown has less carbon nanotube agglomeration than the original carbon nanotube aqueous dispersion and can be better dispersed in the solvent system.

[0042] The carbon nanotube dispersion was placed in a centrifuge tube and centrifuged at 10,000 rpm for 10 min. The supernatant was poured out, ammonia water was added to disperse the precipitated carbon nanotubes, and the dispersion was dropwise applied to a glass substrate and dried on a 60°C hot plate for 3 h to obtain a carbon nanotube film.

[0043] like Figure 2 Shown is a photograph of the lignin-carbon nanotube film obtained by centrifugation.

[0044] like Figure 3 As shown, the scanning electron microscope of the lignin-carbon nanotube film prepared in Example 1 shows that the carbon nanotubes are evenly dispersed, the clusters are reduced, and the surface of the film is relatively smooth.

[0045] The product obtained in Example 1 was tested by the above test method and its conductivity was 1000 S cm -1 , Seebeck coefficient is 45.1μVK -1 , the power factor is increased to 203.4μWm -1 K -2 . See Table 1 for details.

[0046] Among them, the original carbon nanotube film was prepared as the control group, 6 mg of single-walled carbon nanotubes were added to 2 mL of 0.5 M ammonia solution, and after mixing evenly, a cell crusher was used to ultrasonically ultrasonicate at 150 W power for 5 minutes to obtain a carbon nanotube dispersion. The carbon nanotube dispersion was dropwise coated on a glass substrate and placed on a 60°C hot plate to dry for 3 hours to obtain a carbon nanotube film, which was the original carbon nanotube film.

[0047] Table 1: Comparison of thermoelectric properties of pristine carbon nanotubes and lignin-carbon nanotube films (Example 1)

[0048] <![CDATA[Conductivity / Scm -1 > <![CDATA[Seebeck coefficient / μVK -1 > <![CDATA[Power factor / μWm -1 K -2 > original 702 27.8 54.3 Example 1 1000 45.1 203.4

[0049] As shown in Table 1, the conductivity and Seebeck coefficient of the lignin-carbon nanotube film prepared in Example 1 are significantly higher than those of the original carbon nanotubes, and the power factor of the carbon nanotubes is increased from the initial 54.3 μWm -1 K -2 Increased to 203.4μWm -1 K -2 The carbon nanotube raw material of the lignin-carbon nanotube film is consistent with the original carbon nanotube mentioned in Example 1.

[0050] Example 2: Add 0.3 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 h to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically ultrasonicate at 150 W power for 5 min to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at a speed of 10,000 rpm for 10 min. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 h to obtain a lignin-carbon nanotube film.

[0051] The product obtained in Example 2 was tested by the above test method and its conductivity was 889S cm -1 , Seebeck coefficient is 41.9μVK -1 , the power factor is increased to 156.1μWm -1 K -2 .

[0052] Example 3: Add 0.5 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 h to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W for 5 min to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at 10,000 rpm for 10 min. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 h to obtain a lignin-carbon nanotube film.

[0053] The product obtained in Example 3 was tested by the above test method and its conductivity was 985 S cm -1 , Seebeck coefficient is 43.2μVK -1 , the power factor is increased to 183.8μWm -1 K -2 .

[0054] Example 4: Add 1.5 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 h to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically ultrasonicate at 150 W power for 5 min to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at a speed of 10,000 rpm for 10 min. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the carbon nanotube dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 h to obtain a lignin-carbon nanotube film.

[0055] The product obtained in Example 4 was tested by the above test method and its conductivity was 1046S cm -1 , Seebeck coefficient is 36.6μVK -1 , the power factor is increased to 140.1μWm -1 K -2 .

[0056] Example 5: Add 2 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 h to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W power for 5 min to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at a speed of 10,000 rpm for 10 min. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the carbon nanotube dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 h to obtain a lignin-carbon nanotube film.

[0057] The product obtained in Example 5 was tested by the above test method and its conductivity was 960 S cm-1 , Seebeck coefficient is 35.4μVK -1 , the power factor is increased to 120.3μWm -1 K -2 .

[0058] Example 6: Add 2.5 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 h to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically ultrasonicate at 150 W power for 5 min to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at a speed of 10,000 rpm for 10 min. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the carbon nanotube dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 h to obtain a lignin-carbon nanotube film.

[0059] The product obtained in Example 6 was tested by the above test method and its conductivity was 903S cm -1 , Seebeck coefficient is 34.1μVK -1 , the power factor is increased to 105.0μWm -1 K -2 .

[0060] Example 7: Add 3 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 h to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W for 5 min to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at 10,000 rpm for 10 min. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the carbon nanotube dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 h to obtain a lignin-carbon nanotube film.

[0061] The product obtained in Example 7 was tested by the above test method and its conductivity was 848 S cm -1 , Seebeck coefficient is 32.4μVK -1 , the power factor is increased to 89.0μWm -1 K -2 .

[0062] Example 8: Add 3.6 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 h to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W for 5 min to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at 10,000 rpm for 10 min. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the carbon nanotube dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 h to obtain a lignin-carbon nanotube film.

[0063] The product obtained in Example 8 was tested by the above test method and its conductivity was 725 S cm -1 , Seebeck coefficient is 30.5μVK -1 , the power factor is increased to 67.4μWm -1 K -2 .

[0064] Example 9: Add 4 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 h to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W for 5 min to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at 10,000 rpm for 10 min. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the carbon nanotube dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 h to obtain a lignin-carbon nanotube film.

[0065] The product obtained in Example 9 was tested by the above test method and its conductivity was 618 S cm -1 , the Seebeck coefficient is 28.6μVK -1 , the power factor is increased to 50.5μWm -1 K -2 .

[0066] Example 10: Add 5 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 hours to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W power for 5 minutes to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at a speed of 10,000 revolutions per minute for 10 minutes. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the carbon nanotube dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 hours to obtain a lignin-carbon nanotube film.

[0067] The product obtained in Example 10 was tested by the above test method and its conductivity was 527 S cm-1 , Seebeck coefficient is 27.0μVK -1 , the power factor is increased to 38.4μWm -1 K -2 .

[0068] Example 11: Add 1 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 h to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W for 5 min to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at 10,000 rpm for 30 min. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 h to obtain a carbon nanotube film.

[0069] The product obtained in Example 11 was tested by the above test method and its conductivity was 929S cm -1 , Seebeck coefficient is 44.5μVK -1 , the power factor is increased to 184.0μWm -1 K -2 .

[0070] Example 12: Add 1 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 h to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W for 5 min to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at 10,000 rpm for 5 min. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 h to obtain a carbon nanotube film.

[0071] The product obtained in Example 12 was tested by the above test method and its conductivity was 1023 Scm -1 , Seebeck coefficient is 45.0μVK -1 , the power factor is 207.2μWm -1 K -2 .

[0072] Example 13: Add 1 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 hours to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W for 5 minutes to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at 5000 rpm for 5 minutes. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 hours to obtain a carbon nanotube film.

[0073] The product obtained in Example 13 was tested by the above test method and its conductivity was 1015 Scm -1 , Seebeck coefficient is 45.2μVK -1 , the power factor is 207.4μWm -1 K -2 .

[0074] Example 14: Add 1 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 hours to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W for 5 minutes to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at 5000 rpm for 30 minutes. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 hours to obtain a carbon nanotube film.

[0075] The product obtained in Example 14 was tested by the above test method and its conductivity was 945 S cm -1 , Seebeck coefficient is 44.6μVK -1 , the power factor is increased to 188.0μWm -1 K -2 .

[0076] Example 15: Add 1 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 hours to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W for 5 minutes to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at 12,000 rpm for 30 minutes. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 hours to obtain a carbon nanotube film.

[0077] The product obtained in Example 15 was tested by the above test method and its conductivity was 827 S cm -1, Seebeck coefficient is 42.8μVK -1 , the power factor is increased to 151.5μWm -1 K -2 .

[0078] Example 16: Add 1 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 hours to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W for 5 minutes to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at 12,000 rpm for 5 minutes. Pour out the supernatant, add ammonia water to disperse the precipitated carbon nanotubes, and apply the dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 hours to obtain a carbon nanotube film.

[0079] The product obtained in Example 16 was tested by the above test method and its conductivity was 1027 Scm -1 , Seebeck coefficient is 44.8μVK -1 , the power factor is increased to 206.1μWm -1 K -2 .

[0080] Example 17-Example 25:

[0081] Referring to the preparation method of Example 1, lignin was added to 2 mL of 0.5 M ammonia solution and stirred at room temperature for 3 h to obtain a lignin solution. Carbon nanotubes were added to the lignin solution, and after mixing evenly, a cell crusher was used to ultrasonically ultrasonicate at a power of 150 W for 5 min to obtain a stably dispersed carbon nanotube dispersion, and then the dispersion was directly drop-coated on a glass substrate and placed on a 60° C. hot plate for drying for 3 h to obtain a carbon nanotube film.

[0082] Furthermore, in Examples 17-25, there are differences in the mass ratio of lignin to carbon nanotubes. Under different lignin to carbon nanotube usage ratios, the thermoelectric properties of the obtained products were measured by the above test method, including parameters such as conductivity, Seebeck coefficient and power factor. See Table 2 for details:

[0083] Table 2: Preparation conditions and properties of lignin-carbon nanotube films in Examples 17-25

[0084]

[0085]

[0086] Example 26: Add 1 mg of polystyrene sulfonic acid (PSSH) to 2 mL of water and stir at room temperature for 3 hours to obtain a polystyrene sulfonic acid solution. Add 6 mg of carbon nanotubes to the polystyrene sulfonic acid solution, mix well, and use a cell crusher to ultrasonically sonicate at 150 W power for 5 minutes to obtain a stably dispersed carbon nanotube dispersion. Place the carbon nanotube dispersion in a centrifuge tube and centrifuge at a speed of 10,000 rpm for 10 minutes. Pour out the supernatant, add water to disperse the precipitated carbon nanotubes, and apply the dispersion droplets to a glass slide substrate, place it on a 60°C hot plate and dry it for 3 hours to obtain a polystyrene sulfonic acid-carbon nanotube film.

[0087] The product obtained in the embodiment was tested by the above test method and its conductivity was 3500 S cm -1 , Seebeck coefficient is 18.1μVK -1 , the power factor is increased to 114.7μWm-1K -2 .

[0088] Example 27: Add 1 mg of lignin to 2 mL of 0.5 M ammonia solution and stir at room temperature for 3 h to obtain a lignin solution. Add 6 mg of carbon nanotubes to the lignin solution, mix well, and then use a cell crusher to ultrasonically ultrasonicate at 150 W power for 5 min to obtain a stably dispersed carbon nanotube dispersion. Filter the carbon nanotube dispersion to remove the lignin solution and wash it twice with ammonia water. Place the carbon nanotube film prepared by filtration on a 60°C hot plate and dry for 3 h to obtain a lignin-carbon nanotube film.

[0089] The product obtained in the embodiment was tested by the above test method and its conductivity was 221S cm -1 , Seebeck coefficient is 50.9μVK -1 , the power factor is 57.3μWm -1 K -2 .

[0090] Embodiment 28:

[0091] Based on Example 1, the lignin removed by centrifugation in Example 1 was collected and weighed. It can be seen that the amount of lignin removed in Example 1 is 0.1 mg, that is, the amount of lignin added is 0.9 mg, and when the amount of lignin / carbon nanotube added is 0.9:6, the data of the example are as follows:

[0092] 0.9 mg of lignin (molecular weight 3600) was added to 2 mL of 0.5 M ammonia solution and stirred at room temperature for 3 h to obtain a lignin solution. 6 mg of single-walled carbon nanotubes were added to the lignin solution, mixed evenly, and then ultrasonicated with a cell crusher at 150 W power for 5 min to obtain a stably dispersed carbon nanotube dispersion. The carbon nanotube dispersion was dropwise applied to a glass substrate and dried on a 60 ° C hot plate for 3 h to obtain a lignin-carbon nanotube film. The lignin-carbon nanotube film prepared when the lignin / carbon nanotube addition ratio was 0.9:6 was measured by the above test method, and its conductivity was 1034 S cm -1 , Seebeck coefficient is 34.8μVK -1 , the power factor is increased to 125.2μWm -1 K -2 .

[0093] In summary, the raw materials, raw material amounts and thermoelectric properties in the above embodiments are shown in Table 3:

[0094] Table 3: List of raw materials, raw material amounts and thermoelectric properties in the above examples

[0095]

[0096]

[0097] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these changes and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention, and the protection scope of the present invention shall be subject to the claims.

Claims

1. A method for preparing a carbon nanotube film with high thermoelectric performance, characterized in that: The steps include: The carbon nanotubes and the lignin solution are uniformly mixed and ultrasonically dispersed to obtain a carbon nanotube dispersion; The carbon nanotube dispersion is centrifuged until the carbon nanotubes in the carbon nanotube dispersion are precipitated, the supernatant is removed, the carbon nanotubes are dispersed in a solvent, and the solvent is drop-coated on a glass substrate, and dried to obtain a carbon nanotube film.

2. The method for preparing a carbon nanotube film with high thermoelectric performance according to claim 1, characterized in that: The mass ratio of the lignin to the carbon nanotubes is (0.05-0.6):

1.

3. The method for preparing a carbon nanotube film with high thermoelectric performance according to claim 1, characterized in that: The mass concentration of the lignin solution is 0.1-3 mg / mL; the molecular weight of the lignin solution is 500-10000.

4. The method for preparing a carbon nanotube film with high thermoelectric performance according to claim 1, characterized in that: The lignin solution is obtained by dissolving lignin in an alkaline solution to prepare a lignin solution; The alkaline solution is one of sodium hydroxide, potassium hydroxide and ammonia water, and the concentration of the alkaline solution is 0.1-1M.

5. The method for preparing a carbon nanotube film with high thermoelectric performance according to claim 1, characterized in that: The carbon nanotubes are one or more of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes; the inner diameter of the carbon nanotubes is less than 2 nm, and the length is 5-30 μm.

6. The method for preparing a carbon nanotube film with high thermoelectric performance according to claim 1, characterized in that: The power of the ultrasonic dispersion is 70-300W, and the ultrasonic time is 1-60min.

7. The method for preparing a carbon nanotube film with high thermoelectric performance according to claim 1, characterized in that: The centrifugal speed is 5000-12000 r / min, and the time is 1-30 min.

8. The method for preparing a carbon nanotube film with high thermoelectric performance according to claim 1, characterized in that: The solvent is water or an alkaline solution.

9. The method for preparing a carbon nanotube film with high thermoelectric performance according to claim 1, characterized in that: The drying temperature is 60-100° C. and the drying time is 1-5 hours.

10. A carbon nanotube film with high thermoelectric performance obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Highly Stable Environmentally Friendly Aqueous Dispersion of Carbon Nanotubes and Its Preparation Method

    CN108609611B

  • Method for improving stability of carbon nanotubes

    CN111559742A